CD28 co-stimulation is dispensable for the steady state homeostasis of intestinal regulatory T cells - Wakamatsu, Ei; Omori, Hiroki; Tabata, Yuki; Akieda, Yuki; Watanabe, Shiho; Ogawa, Shuhei; Abe, Ryo (International immunology, 2018)
Abstract It is well-established that CD28 co-stimulation is required for the development and the proliferation of thymus-derived regulatory T cells (tTregs). Meanwhile, the role of CD28 co-stimulation in the homeostasis of peripherally derived Tregs (pTregs) remains unclear. To clarify this issue, we analyzed Tregs in small and large intestines (SI and LI), the principle sites of pTreg development. Interestingly, and different from in the thymus, Tregs were abundant in the intestines of CD28−/− mice, and most of them were phenotypically pTregs. We showed that CD28−/− naive T cells differentiated into pTregs in the LI after oral exposure to antigens and that CD28−/− pTregs in the LI had the same highly proliferative activity as CD28+/− cells. CD28−/− pTregs acquired these Treg-specific features at transcriptional and epigenetics levels. On the other hand, some immune suppressive molecules were down-regulated in CD28−/− pTregs. Correspondingly, the suppressive activity of CD28−/− pTregs was weaker than CD28+/+ cells. These results indicate that the homeostasis of pTregs in the intestines is maintained even in the absence of CD28, whereas CD28 is required for the maximal suppressive activity of intestinal pTregs. Lack of CD28 does not affect gut pTreg numbers but weakens their suppressive function